EFEKTIVITAS PERATURAN DAERAH KABUPATEN BANDUNG TENTANG PARIWISATA HALAL: STUDI PEMAHAMAN MASYARAKAT DAN PELAKU USAHA - Pramadika, Taukhid; Daffa, Marthias; Rahmafitria, Fitri; Prabowo, Panji Alam (Universitas Mathla’ul Anwar Banten, 2025)
Halal tourism is a rapid emerging concept in the tourism sector that offers substantial development opportunities, particularly in a country with Muslim majority such as Indonesia. This concept encompasses the provision of products and services aligning with sharia principles, including accommodation, transportation, culinary, and tourist activities. Despite the potential, the implementation of halal tourism in Indonesia, particularly in Bandung Regency faces several challenges such as limited understanding from peoples of halal tourism concept, insufficient socialization from the government, difficulties in halal certification standards among tourism business industries, and the complexity related to the policies. This study aims to analyze the understanding of the community and business industries in the development of halal tourism in Bandung Regency. By using a qualitative method with policy analysis approach, this research identifies challenges and opportunities in implementing halal tourism. The data were collected through in-depth interviews with business actors, local community, and stakeholders, as well as an analysisi of regulatory documents, including Regional Regulations of Bandung Regency on Halal Tourism. Additionally, a comparative analysis of halal tourism policies between Indonesia and Thailand, was conducted to identify the differences in conceptual and implementation. The findings indicate that the community predominantly associates halal tourism with prayer’s facilities and culinary offerings, while other aspects such as accommodation, activities, and services remain unexplored. Business actors encounter significant challenges in obtaining halal certification due to bureaucratic complexity and high costs. This study emphasizes the importance of an inclusive approach from the government to enhance public and business understanding, thereby fostering the sustainable development of halal tourism in Bandung Regency.